114k views
1 vote
F(x) =2x-4 and g(x) =-3x+2 find: f(g(x))

User Linuslabo
by
4.0k points

1 Answer

2 votes

Answer:


f(g(x))=-6x

Explanation:

Composite Function

Given f(x) and g(x) as real functions, the composite function named
(f\circ g)(x) is defined as:


(f\circ g)(x)=f(g(x))

It can simply be found by substituting g into f.

Our functions are:


f(x)=2x-4


g(x)=-3x+2

Substituting g into f:


f(g(x))=2(-3x+2)-4

Operating:


f(g(x))=-6x+4-4

Simplifying:


\boxed{f(g(x))=-6x}

User Hiren Patel
by
4.7k points